The semantics of ditransitive construction in a diachronic perspective - Furtado da Cunha, Maria Angélica (2020)
This paper focuses on the ditransitive construction of Brazilian Portuguese, aiming at examining its semantic evolution. To this end, it compares manifestations of this construction in the 18th and 20th centuries in order to investigate whether there has been a change in its morphosyntax and in the semantic class of the verbs that instantiate it. The theoretical approach combines assumptions and analytical categories of Usage-based Functional Linguistics (FURTADO DA CUNHA, M. A.; BISPO, E. B.; SILVA, 2013a) and Construction Grammar (GOLDBERG, 1995; TRAUGOTT; TROUSDALE, 2013). The results led to the conclusion that, in the 18th as well as in the 20th century, the ditransitive construction prototypically conceptualizes an event of physical transfer, in which an animate participant (Subject) transfers an object (Direct Object) to a human entity (Indirect Object). Furthermore, there was no change in the semantic class of verbs that can instantiate extensions from the central meaning of this construction.